Paradigma Geopolitik Indonesia ditangan Generasi Z : Menuju Demokrasi Emas - Yandari, Eka Azzafitri (Maliki Interdisciplinary Journal, 2025)
Generation Z serves as a socio-political actor with a strategic role in determining the geopolitical direction of Indonesia Emas 2045. The main issue examined in this journal is to what extent Generation Z with its digital-native character, critical thinking, and inclusivity can contribute strategically to strengthening democracy and national geopolitical stability. Born in the digital era, Generation Z possesses advanced technological skills, strong social awareness, and a tendency to think critically and embrace diversity. Their active involvement in political processes can serve as a solid foundation for the realization of a Golden Democracy that is just, open, people-centered, and sustainable. Therefore, the active participation of Generation Z in democratic processes may become a key pillar in achieving a fair, participatory, and sustainable democracy. With systematic support from the state, educational institutions, and civil society, Generation Z can serve as the main driver of Indonesia’s geopolitical transformation toward a sovereign and democratic future.